2012
DOI: 10.1128/jcm.01225-12
|View full text |Cite
|
Sign up to set email alerts
|

Probability of Negative Mycobacterium tuberculosis Complex Cultures Based on Time to Detection of Positive Cultures: a Multicenter Evaluation of Commercial-Broth-Based Culture Systems

Abstract: We conducted a multicenter study to determine whether Mycobacterium tuberculosis complex (MTBC) cultures in automated broth-based systems could reliably be considered negative sooner than 6 weeks. Laboratory sites used Bactec MGIT or BacT/Alert and tracked results of time to detection of all mycobacteria (TTD-all, n = 1547) and of MTBC (TTD-MTBC, n = 466) over 6-month periods from primarily (93%) respiratory specimens. Cumulative percentag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 20 publications
0
21
1
Order By: Relevance
“…This may delay physician decisions and limit laboratory capacity. Studies from Switzerland and the U.S., low TB burden countries, suggested that the incubation time of MGIT cultures could be shortened from six weeks [9, 10]. We sought to test this hypothesis in a setting with a high incidence of TB and HIV infection.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This may delay physician decisions and limit laboratory capacity. Studies from Switzerland and the U.S., low TB burden countries, suggested that the incubation time of MGIT cultures could be shortened from six weeks [9, 10]. We sought to test this hypothesis in a setting with a high incidence of TB and HIV infection.…”
mentioning
confidence: 99%
“…Pfyffer and Wittwer in a smaller study from Switzerland found that 50% of their MGIT cultures for MTB complex became positive within 14 days, concluding that a final report of a negative culture could be issued after 4 weeks of incubation [9]. In a multicenter study of 366 MTB complex positive MGIT cultures done at 9 U.S. laboratories, Tyrrell et al reported that 99.4% of diagnostic specimens were detected by week 4, concluding that a negative culture could reliably be reported at 4 weeks for diagnostic specimens and 5 weeks for follow-up specimens [10]. Our analysis, based on a much larger number of MTB complex positive sputum cultures collected over 8 years in a high TB incidence country, confirms the findings of these studies.…”
mentioning
confidence: 99%
“…The time to detection of a positive culture with MGIT was found to be shorter than with LJ or TLA, in accordance with the results of previous studies. [5][6][7][8][9][10][11][12][13][14] Furthermore, Balabanova et al reported that the concordance between drug susceptibility testing on LJ and MGIT was 96.8% for rifampicin and 95.6% for isoniazid. 28 There are new molecular techniques that perform well, allowing diagnosis on the same day, with the added advantage of providing information about resistance to isoniazid and/or rifampicin.…”
Section: Discussionmentioning
confidence: 99%
“…These methods have been shown to decrease the mean time to detection of growth to 11-15.1 days. 5,6,9,[11][12][13][14] The method of obtaining a respiratory sample is also critical. In prisons, it is important to employ alternative strategies to obtain a specimen when the patient cannot expectorate or has inadequate sputum (HIV patients or those with a dry cough), during follow-up to confirm that the patient is cured, or for people who are sputum smear-negative.…”
Section: Introductionmentioning
confidence: 99%
“…Rapid diagnosis of TB is critical for initiating effective treatment and preventing its transmission in the community [1]. Recent advances in molecular methods have shortened the turnaround time for the identification of Mycobacterium tuberculosis (MTB); however, culture is still essential for phenotypic drug susceptibility testing and improving the case detection of smear negative patients [1, 2]. Due to the slow growth rate, conventional solid culture systems including Löwenstein-Jensen (LJ) slant or Middlebrook 7H11 agar plate always require 8 weeks of incubation before a negative result is reported, which cannot meet the criteria of clinical practice [3].…”
Section: Introductionmentioning
confidence: 99%